The Policy Think Tank in Lao PDR: Building evidence-based research capacity and science policy interfaces - Phounvisouk, L.; Victor, Michael; Sonethavixay, Sengphachanh (International Livestock Research Institute, 2023)
The purpose of this case study is to draw lessons from the PTT for design of future research policy platforms or networks. The study provides an overview of the institutional context within which the PTT was established and carried out its work, reviews the organizational structure and functions of the think tank and presents some of the selected research activities that were carried out, plus their impacts. Finally, the case study draws out some lessons for future consideration when establishing science to policy platforms.